A state machine strategy based on droop control for an energy management system of PEMFC-battery-supercapacitor hybrid tramway. (28th September 2016) - Li, Qi; Yang, Hanqing; Han, Ying; Li, Ming; Chen, Weirong
Abstract: In this paper, a hybrid powertrain configuration which consists of multiple proton exchange membrane fuel cell (PEMFC) systems, batteries and supercapacitors (SCs) is developed for LF-LRV tramway. A state machine strategy based on droop control is proposed to coordinate multiple power sources, avoid the transients and rapid changes of power demand, and achieve high efficiency without degrading the mechanism performance for an energy management system of hybrid tramway. A hybrid system model of tramway is established with commercially available devices, and then the proposed energy management strategy is evaluated with a real driving cycle of tramway from Turkey. The results demonstrate that the proposed strategy is able to coordinate multiple power sources based on their natural characteristics, satisfy rapid changes of the power demand and achieve high efficiency of overall tramway. Hence, the proposed energy management strategy for high-power hybrid tramway will improve the hydrogen consumptions of overall hybrid system and the efficiencies of each power source. Highlights: A hybrid system model of tramway is established with commercially available devices. A droop control is employed to guarantee the bus voltage stability. A state machine strategy is proposed to coordinate multiple power sources. The results demonstrate that the proposed strategy can coordinate multiple power sources and achieve high efficiency.